A Return to Librarian Mediated Searching in A Pilot Systematic Search Service. Issue 2 (2nd April 2020) - Russell, Fiona; Muir, Rebecca
ABSTRACT: Systematic and systematic-like reviews are an important aspect of healthcare research, and are increasingly being employed in other disciplines such as marketing and education. They require a high skill level to effectively conduct the often complex searches that are a core component of the review process. With guidelines encouraging the inclusion of librarians in systematic review teams, researchers are increasingly seeking out the involvement of librarians in this capacity. Subsequently, many libraries have begun deliberating on mediated search services to meet this need, a return to the days of the librarian-mediated database search. In 2018–2019, members of the Deakin University Library Health Liaison team were approached by a research team to develop and run searches for a scoping review, a systematic-like review designed to identify the size and scope of literature for an issue of interest. A pilot was subsequently developed for a mediated searching service. Lessons learnt and workflows developed have formed the basis of a more extensive tiered systematic searching service model (incorporating mediated searching) which is being trialled in 2020.